Analisis Kandungan Silikon Karbida (SiC) Sebagai Filler Terhadap Peningkatan Kekerasan Pada Metal Matrik Komposit - Muhammad Ghazali Arrahim; Leo Hutri Wicaksono; Muhammad Syaiful Fadly; Afrizal Abdi Musyafiq (P3M Politeknik Negeri Cilacap, 2023)
Metal Matrix Composite is one of the metal composites that utilize aluminum alloy as a matrix in its fabrication. MMC has better specifications than the conventional materials it forms because it is light, ductile, with better hardness properties. The aluminum alloy as the matrix in this study has good mechanical properties but relatively low hardness values, especially type 2xxx aluminum containing Al-Cu or duralumin. By adding silicon carbide (SiC) ceramic content which acts as a filler in the manufacture of MMC it aims to increase the hardness value through a strengthening mechanism by analyzing the distribution of filler particles to the matrix. Using the sintering method with temperature variations that affect the mechanical properties of MMC. From the tests carried out the MMC specimens experienced an increase of 7.06% with the highest hardness value at 300oC sintering temperature of 71.6 HRB. With a SiC content of 14.42% Wt. Then it was observed using a Scanning Electron Microscope (SEM) that the distribution of SiC particles experienced an even distribution and bonded to the aluminum matrix thereby reducing porosity and increasing the hardness value of the MMC material.